Commissioning of the upgraded RICH system at the LHCb experiment. (1st November 2022) - Okamura, S.; ,
Abstract: The Ring-Imaging Cherenkov (RICH) system is an essential element of the LHCb experiment: it consists of an upstream detector (RICH 1), located close to the interaction point, and a downstream detector (RICH 2), placed after the tracking system and has the task of identifying charged hadrons over the momentum range 2–100 GeV/c. Currently, the LHCb experiment is completing an upgrade phase to allow data collection at a five-fold increase in instantaneous luminosity up to 2 × 10 33 cm −2 s −1 and read out data at a rate of 40 MHz. The challenges of the higher luminosity are a significant increase in detector occupancy and a larger radiation dose. To match the new experimental requirements, both RICH detectors have been upgraded with a redesigned opto-electronic chain and new photon detectors. In addition, RICH 1 has a modified layout with new mechanics and spherical mirrors to reduce the maximum occupancy. A summary of the upgrade program and the current status of the commissioning operations will be presented.